Clinical characterization of allostatic overload. (October 2019) - Fava, Giovanni A.; McEwen, Bruce S.; Guidi, Jenny; Gostoli, Sara; Offidani, Emanuela; Sonino, Nicoletta
Highlights: Allostatic load reflects the cumulative effects of stressful experiences in daily life and may lead to disease over time. When the cost of chronic exposure to physiologic responses exceeds the coping resources of an individual, allostatic overload ensues. Clinical criteria for the determination of allostatic overload have been developed. Use of these clinical criteria can broaden dissemination of measures to prevent or decrease the negative impact of toxic stress on health. Abstract: Allostatic load reflects the cumulative effects of stressful experiences in daily life and may lead to disease over time. When the cost of chronic exposure to fluctuating or heightened neural and systemic physiologic responses exceeds the coping resources of an individual, this is referred to as "toxic stress" and allostatic overload ensues. Its determination has initially relied on measurements of an interacting network of biomarkers. More recently, clinical criteria for the determination of allostatic overload, that provide information on the underlying individual experiential causes, have been developed and used in a number of investigations. These clinimetric tools can increase the number of people screened, while putting the use of biomarkers in a psychosocial context. The criteria allow the personalization of interventions to prevent or decrease the negative impact of toxic stress on health, with particular reference to lifestyle modifications and cognitive behavioral therapy.